Kesalahan tata bahasa bidang morfologi pada karangan narasi peserta didik kelas IV semester I sdn tegalsari n0. 60 tahun pelajaran 2019/2020 - Geby Adellestia (Universitas Sebelas Maret, 2020)
This research was carried out at SDN Tegalsari No. 60 Surakarta, precisely at 4th grade students with a total of 24 students. The purpose of this research was to alakyze and describe thee types of grammatical errors in the field of morphology tata exsited in the narrative essay of fourth gade students at SDN Tegalsari No. 60. This type of research is a qualitative study using descriptive methods. Data collection is done by means of observation and using thu method of documentation, interviews, and field notes. Based on the results of grammatical error analysis in the field of morphologythat has been obtained, then the data is processed trough interactive Milles and Huberman data analysis. The data that has been obtained is then grouped into each type and corrects errors and causes the errors. Bese on the results of research, grammatical errors in the filed of morphology in students narrative essays can be divided into 6 types of errors, writing point errors, comma writing errors, writing errors in capital letters, writing errors in invented words, writing errors reduplication words, and errors diction.